Design, simulation, fabrication and control a 3-DOF planar robotic manipulator - Trần Đình Hòa; Nguyễn Văn Khiêm; Trần Đức Thiện (Journal of Technical Education Science, 2021)
This paper aims to study how to fabricate, simulate and control a 3-degree of freedom (DOFs) robot arm that moves flexibly in a plane. First, the design process of the 3-DOFs robot arm model is done on the Solidworks platform. Next, the simulation and calculation of the PD controller of the robot arm are implemented on Matlab-Simulink with Simscape Multibody library to evaluate the effectiveness of the model and the control design. Then, the real model of the robot arm is fabricated with the control box. Finally, a real robot arm was controlled to move following the reference in the plane with the PD controller embedded on the STM32F4 microcontroller and collected data about the computer. By applying this procedure in robot design, it helps to not only minimize the cost and time but also improve the efficiency in the controller design for the robot.